2007
DOI: 10.1016/j.watres.2006.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of drinking water biofilm in flow/non-flow conditions

Abstract: A B S T R A C TDrinking water biofilm formation on polyvinyl chloride (PVC), cross-linked polyethylene (PEX), high density polyethylene (HDPE) and polypropylene (PP) was followed in three different reactors operating under stagnant or continuous flow regimes. After one week, a quasi-steady state was achieved where biofilm total cell numbers per unit surface area were not affected by fluctuations in the concentration of suspended cells. Metabolically active cells in biofilms were around 17-35% of the total cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 40 publications
(49 reference statements)
3
95
2
1
Order By: Relevance
“…Predicting biofilm growth rates is of great interest, and we determined rates using TCC and HPC values and the method proposed by Manuel et al (2007). A biofilm model can be expressed by the following equation, which is based on the assumption that biofilm development reaches a steady state through a balance between growth and detachment (Manuel et al, 2007):…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Predicting biofilm growth rates is of great interest, and we determined rates using TCC and HPC values and the method proposed by Manuel et al (2007). A biofilm model can be expressed by the following equation, which is based on the assumption that biofilm development reaches a steady state through a balance between growth and detachment (Manuel et al, 2007):…”
Section: Resultsmentioning
confidence: 99%
“…A biofilm model can be expressed by the following equation, which is based on the assumption that biofilm development reaches a steady state through a balance between growth and detachment (Manuel et al, 2007):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, biofilms exist on almost all of the solid surfaces exposed to water in the natural environment (White et al 1998;Dong et al 2002;Kang et al 2006;Dong et al 2004;Qin 2008), and microorganisms in the irrigation system can form biofilms. To date, the research on biofilms has been focused on sewage treatment, water supply/drainage, water environment self-purification and biological clogging of porous media (Bishop 2007;Simpson 2008;Gouidera et al 2009;Liu et al 2008;Manuel et al 2007). In contrast, the knowledge about biofilms in drip irrigation systems is much less.…”
Section: Discussionmentioning
confidence: 99%
“…In the natural environment, biofilms exist on almost all of the solid surfaces exposed to water (White et al 1998;Dong et al 2002Dong et al , 2004Kang et al 2006;Qin 2008) and thus have received close attention from researchers in the fields of sewage treatment (Bishop 2007;Simpson 2008) and water supply/drainage (Gouidera et al 2009;Liu et al 2008). To date, research on pipeline biofilms has been focused on the water supply pipeline (Gouidera et al 2009;Liu et al 2008;Manuel et al 2007), whereas the biofilms in irrigation systems have been rarely studied. Although knowledge about biofilms in reclaimed water drip irrigation systems is limited (Li et al 2012a, b), it has been found that biofilm formation was probably the basic cause of the emitter clogging.…”
Section: Introductionmentioning
confidence: 99%